Answer:
a) [tex]A \cap B = A[/tex]
b) [tex]C - B = {}[/tex]
c) [tex]A \cup (B \cap C) = A \cup C = \left\{0,2,3,4,5,6,7,8\right\}[/tex]
Step-by-step explanation:
We have the following universal set
[tex]B = \left\{0,1,2,3,4,5,6, 7,8,9\right\}[/tex]
We also have these following sets:
[tex]A = \left\{0,2,4,6,8\right\}[/tex]
[tex]B = \left\{2,3,5,7\right\}[/tex]
a) [tex]A \cap B[/tex]
[tex]A \cap B[/tex] is the set of elements that belong to both A and B.
B is the universal set, so:
[tex]A \cap B = A[/tex]
b) [tex]C - B[/tex]
[tex]C - B[/tex] is the set with all elements that belong to C and do not belong to B.
B is the universal set, so:
[tex]C - B =\left\{\right\}[/tex]
c) [tex]A \cup (B \cap C)[/tex]
Because of parenthesis, [tex]B \cap C[/tex] takes precedence.
In a), I explained the [tex]\cap[/tex] operation.
B is the universal set, so:
[tex]B \cap C = C[/tex]
Now we have [tex]A \cup (B \cap C) = A \cup C[/tex]
[tex]A \cup C[/tex] is the set formed by the elements that belong to at least one of A or C.
So:
[tex]A \cup (B \cap C) = A \cup C = \left\{0,2,3,4,5,6,7,8\right\}[/tex]